Feed Management on I Made Sukarata Pigs Breeding Livestock in Batu Paras, Padangsambian Kaja Village, District of Denpasar - N.N, Sulastri; Mudita, I M.; Sukanata, I W. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
Pigs are prolific livestock capable of producing large numbers of piglets at one birth. Pigs have many advantages that pigs are very efficient in utilizing feed. Pig is very good in processing the feed to be used as food for humans as in the carcass. With a rough feed the pig is able to grow relatively better. When given a standard ration or feed containing substances in accordance with the needs of life, pigs can reach 0.7-0,8kg / day body weight and some are able to reach up to 1kg / day with 2.5-3kg / day ration consumption so Feed conversion Ratio (FCR) can be between 3.5-3,7. In the management of pigs, one of the most noticed is the feed management. Taking into account the quality and quantity of feed in the ration is one of the most important factors in increasing the growth of livestock and the level of profit earned by the breeder.A good ration is a ration that is able to meet the nutritional needs required by livestock such as water, carbohydrates, fats, proteins, vitamins and minerals. In preparing the rations a variety of things must be considered so that rations can provide good effects for livestock such as the threshold of nutritional needs of the group of pig users, the content of food substances in the diet, the use of nutrients and the availability of materials including the price. In the farm owned by Mr. I Made Sukarata feed given has nutritional content that is still below the standards that will affect the growth and productivity of livestock.With 3kg / day feeding for mains and studs then 4kg / day for old pregnant and breastfeeding parents did not provide maximum growth when pig nutrition did not meet the needs. Liter size from the farm owned by Mr. I Made Sukarata is the range of 8-10 tail with birth weight 1.7-1.8 kg / head and weight loss of wean is 7kg / ekor. The growth of pigs is greatly influenced by the nutrients that depend on the feed. Keywords: Pig, ration and growth.